Differential Item and Distractor Functioning ‎in a Critical Thinking Test among University ‎Students According to Gender - Al-Abd Al‏-‏Qader ‎, Kawthar; Al-Sawalmeh, Yousef (Jordan Journal of Educational Sciences, 2021)
This study aimed to examine gender-related differential item and distractor functioning in a critical- thinking test among university students. The test consisted of (49) four alternative multiple-choice items, covering critical thinking-skills representing: Analysis, interpretation, evaluation, explanation, reasoning, statistical and probabilistic reasoning, identification of assumptions and concentration. The responses of a cluster random sample of (930) male and female students from Yarmouk University and Al-Balqa Applied University were analyzed. Mantel-Haenszel odds ratio method was used to examine differential item and distractor functioning. The results indicated that there were (8) items with differential functioning, in favor of males in (6) items. The size of the differential functioning was small in 4 items, moderate in (3) items and large in one item. Also, there were (11) distractors with differential functioning in favor of males in (7) distractors. The size of differential functioning was large in (2) distractors and moderate in (9) distractors